2019
DOI: 10.3390/ma12121906
|View full text |Cite
|
Sign up to set email alerts
|

Shear Performance Assessment of Sand-Coated GFRP Perforated Connectors Embedded in Concrete

Abstract: In order to evaluate the shear performance of sand-coated glass fiber-reinforced polymer (GFRP) perforated connectors (SCGPC) embedded in concrete, 8 pull-out tests were conducted. Finite element (FE) analysis considering GFRP failure and cohesion between GFRP and concrete of SCGPC were conducted for parametric analysis. Effects of surface treatment, hole’s radius, embedment length, and multi holes were examined. The test and theoretical analysis revealed that the strength of SCGPC is considerably larger than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…As shown in Figure 8 b–f, the ultimate tensile strengths of the claw connectors at anchorage depths of 3–5 cm were 21.14, 24.33, 25.03, 27.48, and 28.53 kN, respectively. As the anchorage depth increased, the tensile strength of the specimens was improved; however, the overall strength and strength base were relatively small, which is similar to the results of a previous study [ 5 ]. When the anchorage depth increased from 3 to 3.5 cm, the ultimate tensile strength of the specimens had the largest increase.…”
Section: Analysis Of Experimental Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…As shown in Figure 8 b–f, the ultimate tensile strengths of the claw connectors at anchorage depths of 3–5 cm were 21.14, 24.33, 25.03, 27.48, and 28.53 kN, respectively. As the anchorage depth increased, the tensile strength of the specimens was improved; however, the overall strength and strength base were relatively small, which is similar to the results of a previous study [ 5 ]. When the anchorage depth increased from 3 to 3.5 cm, the ultimate tensile strength of the specimens had the largest increase.…”
Section: Analysis Of Experimental Resultssupporting
confidence: 88%
“…Jiang et al [ 4 ] evaluated the shear performance of steel-fiber-reinforced polymeric-material joints. Zhihua et al [ 5 ] proposed an empirical formula for predicting the shear strength of glass-fiber-reinforced-plastic (GFRP) open joints through experimental and finite-element parametric analyses. Clay et al [ 6 ] studied the mechanical properties of different materials, such as glass-fiber-composite reinforcement, stainless steel, galvanized steel, basalt-fiber cloth, and carbon-fiber cloth, to quantify their failure modes and shear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding anchor system is mainly composed of the bonding medium and sleeve, and the CFRP prestressed tendons or prestressed strands are anchored by chemical adhesive force, friction force and mechanical bite force. Moreover, studies indicated that sand-coated can further improve the bonding performance of FRP [ 20 , 21 ]. Bonded anchor system has good fatigue resistance and is more suitable for the anchorage of CFRP prestressed tendons or prestressed strands.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced polymer (FRP) composites have been greatly developed worldwide and have become one of the most popular construction materials for repair and rehabilitation and new construction [1][2][3][4][5][6][7][8][9][10]. Pultruded glass fiber reinforced polymer (GFRP) composites are great candidates for newly constructed bridges decks.…”
Section: Introductionmentioning
confidence: 99%